2021
DOI: 10.1103/physrevphyseducres.17.020124
|View full text |Cite
|
Sign up to set email alerts
|

Perceived irrelevance and achievement goals: Two mindset variables within attitudinal experiences of life science majors in introductory physics

Abstract: In a previous study, students' self-expressed learning orientations towards an exercise centered on self-monitoring one's ability to solve a pre-lab physics problem were identified from a post-test feedback survey given to an introductory algebra-based physics student population spanning six measured semesters, and examined as a potential variable in course performance, force and motion conceptual understanding, and attitudes towards learning physics. The sampled population, which primarily consists of life sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Perceived irrelevance and perceived lack of relevance are the two main reasons why many hospitality students are not interested in math. Many students feel that math has no bearing on their future employment, which makes them uninterested [29] . Similarly, this study found out that for non-math enthusiasts, mathematics are irrelevant to their personal or professional lives, particularly if they are pursuing careers that value communication and language skills more than numbers.…”
Section: Perceived Irrelevancementioning
confidence: 99%
“…Perceived irrelevance and perceived lack of relevance are the two main reasons why many hospitality students are not interested in math. Many students feel that math has no bearing on their future employment, which makes them uninterested [29] . Similarly, this study found out that for non-math enthusiasts, mathematics are irrelevant to their personal or professional lives, particularly if they are pursuing careers that value communication and language skills more than numbers.…”
Section: Perceived Irrelevancementioning
confidence: 99%